Faculty Satisfication Regarding Modular Teaching - Inayat ur Rahman, Sumreena Mansoor, Lubna Meraj, Mumtaz Ahmad, Mobina Ahsan Dodhy, Hina Sattar (Journal of Rawalpindi Medical College, 2022)
Introduction: Recently many medical institutes have been shifted to integrated curriculum; however, the implementation of integrated curriculum has faced problems due to both faculty and student’s satisfaction. Though faculty gives value to it, still certain believe that it’s not as effective as the traditional system. This study aims to evaluate the satisfactory level regarding modular teaching among faculty members at three different medical institutes in Pakistan. Material and Methods: This was a descriptive study where the senior faculty members from three different medical institutes were included. After written consent from participants the data was collected through semi-structured questionnaire. Total of 88 faculty members were included through convenient sampling technique. Data analyzed by SPSS version-22. Results: Overall 50% participants agreed that strength of modular teaching is the integration process & clinical application. 38% agreed that modular teaching provides better understanding & clarity of concepts. Regarding weaknesses 44% agreed that modular teaching requires more trained faculty, 27% said that more resources are required. On the other hand, 84% showed satisfaction that students get more benefits from modular teaching as compare to conventional teaching & 72% agreed that teacher biasness is less, 82% agreed that students become a lifelong learner, 85% agreed that more applied knowledge is delivered through this system. Conclusion: The majority of participating faculties were satisfied with modular teaching as it has a good clinical application, provides better understanding & a student-centered approach.